Analysis Of Structural Assurance, Integrity, Easy of Use And Brand Image On Trust In Use Of P2P Lending - Dewi, Cynthia Sari; Dominggus, Aldi (IJBLE Scientific Publications Community Inc., 2024)
Peer to Peer (P2P) lending has a role as an intermediary platform for lenders and borrowers to conduct transactions without having to go through bank. However, so many P2P Lending cases that reduce public confidence in using P2P Lending. Gradana is one of the P2P lending companies registered with the Financial Services Authority (OJK). Although P2P lending investors have decisions that refer to adverse selection, Gradana shows good performance. This study aims to analyse the factors that influence trust in using P2P lending by adopting trust theory. The sample was 100 respondents from retail investors in Indonesia. The study using SmartPLS4 software. The results showed that integrity has a positive influence and significant on trust in use, while brand image, ease of use and structural assurance has no positive impact on trust in use. The results are expected as reference for companies in increasing the trust of P2P lending users.